Menumbuhkan Kreativitas dan Kemandirian Anak Sejak Usia Dini - Muhammad Idrus (EL-TARBAWI, 2003)
Today we see many parent want their children totakea short course, like English course, etc, and in the other hand they prohibited their children spent all their time for playing. Many parent make rationalization that all of their children's activity is for their children's future. They forgot, or sometime ignorance that all of their children's activity just the way for parent to reach something that they could not reach when they were child. Playing is very urgent for all children to make relationship with peers, grow up their creativity and self help. Parents must give their children time for playing, whatever he or she does.